The effect of educational exercises using the sequencing method according to procedural learning theory to learn the skills of suppression and scoring in football (Damu Journal of Sport Sciences, 2024)
The study aimed to prepare an educational curriculum using the sequential method in accordance with the theory of (procedural learning) to learn the skills of suppression and scoring in football and to identify the effect of educational exercises. The researcher assumed that there were significant statistical differences between the arithmetic averages of the experimental and control groups in the post-tests and in favor of the post-test. The researcher used the method the two experimental groups were equal with pre- and post-tests to achieve the objectives of the study and contribute to solving the research problem. The research population was determined intentionally, while the research sample was chosen randomly using a lottery and was represented by the students of the first stage in the Department of Physical Education and Sports Sciences / College of Basic Education / Al-Mustansiriya University, which numbered in number. (50) Students were divided into two groups (experimental and control), each group having (25) students. The researcher concluded that the educational curriculum had a positive impact on learning the skills (suppression and scoring) in football. The researcher recommended the need to benefit from the special method of study to learn football skills in particular and sports skills in particular.